Transverse polarization measurement of Λ hyperons in pNe collisions at √sNN = 68.4 GeV with the LHCb detector - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2024)
A measurement of the transverse polarization of the Λ andΛ hyperons in pNe fixed-target collisions at √sNN = 68.4 GeV is presented using data collected by the LHCb detector. The polarization is studied using the decay Λ → pπ− together with its charge conjugated process, the integrated values measured are PΛ = 0.029 ± 0.019 (stat) ± 0.012 (syst), PΛ = 0.003 ± 0.023 (stat) ± 0.014 (syst). Furthermore, the results are shown as a function of the Feynman x variable, transverse momentum, pseudorapidity and rapidity of the hyperons, and are compared with previous measurements.